Interannual variation and chemical characterization of major water-soluble inorganic ions in snow across Northwest China - Zhang, Yuxuan; Wang, Ninglian; Zhang, Bo; Zhang, Wei; Shen, Baoshou (Frontiers in Earth Science, 2023)
From November 2018 to April 2020, 438 snow samples were collected near two field observation sites in Heihe and Altay, Northwest China, and the pH and major water-soluble inorganic ions (Ca2+, SO42−, Na+, NO3−, Cl−, K+, Mg2+, and NH4+) were analyzed. To identify the source of ions, the enrichment factor method, Pearson correlation analysis, and HYSPLIT (Hybrid Single Practical Lagrangian Integrated Trajectory) backward trajectory analysis were employed. The snow was nearly pH neutral, and Ca2+ was the dominant cation present. The anion concentration demonstrated high variability. Affected by geographical location and atmospheric circulation, the concentration of soluble inorganic ions in snow from the Altay region was higher than that in the Heihe region and remote areas at high altitude or high latitude. Compared with 2018/2019, ion concentrations in snow increased in 2019/2020, especially in the Altay region. Moreover, the temporal trend of ion concentrations was stable, indicating that the source and migration path of ions had strong consistency. Our study suggested that terrestrial sources are the main driving factors for the ions observed in snow samples from Northwest China, and some ions are also the result of anthropogenic sources (NH4+, SO42−, and NO3−), marine sources (Cl− and Na+), and salt mine dust (Cl−, Na+, SO42−, and K+).